2018
DOI: 10.1063/1.5007854
|View full text |Cite
|
Sign up to set email alerts
|

Upside/Downside statistical mechanics of nonequilibrium Brownian motion. I. Distributions, moments, and correlation functions of a free particle

Abstract: Statistical properties of Brownian motion that arise by analyzing, separately, trajectories over which the system energy increases (upside) or decreases (downside) with respect to a threshold energy level are derived. This selective analysis is applied to examine transport properties of a nonequilibrium Brownian process that is coupled to multiple thermal sources characterized by different temperatures. Distributions, moments, and correlation functions of a free particle that occur during upside and downside e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…These issues were observed with different integrators, RK4, BBK and the VEC. Insights on the poor performance of the interface currents could be achieved based on the upside/downside statistical analysis suggested in Refs 59,60 . While so far much effort had been placed on comparing the performance of different integrators, here we emphasize that using different working definitions for an observable may result in different convergence behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These issues were observed with different integrators, RK4, BBK and the VEC. Insights on the poor performance of the interface currents could be achieved based on the upside/downside statistical analysis suggested in Refs 59,60 . While so far much effort had been placed on comparing the performance of different integrators, here we emphasize that using different working definitions for an observable may result in different convergence behavior.…”
Section: Discussionmentioning
confidence: 99%
“…(92) Figure 9 shows the dependence of these heat ratios on t. The variance in the simulation results shown in Fig. 9 for small t is a consequence of the underlying probability densities being independent of t in the t ′ → t limit, which means that over small time-intervals the probability density changes rapidly to go from the initial distribution ρ 0 at t ′ = 0 to the distribution at t ′ = t. 30 This leads to increased variance in the results from simulation. We have confirmed that simulation results converge to the analytical results with increased sampling.…”
Section: Energy Partitioningmentioning
confidence: 99%
“…which can be applied to construct expressions for the moments and time-correlation functions of a nonequilibrium Brownian process driven by N thermal sources. Because it is proportional to the energy E of the system, the second moment 30,59 v…”
Section: System Details: Brownian Motion Driven By N Thermal Sourcesmentioning
confidence: 99%
See 2 more Smart Citations